Implemetasi Program Berugak Belajar Guna Meningkatkan Kemampuan Literasi Peserta Didik di SDN 3 Masbagik Utara - Hadi, M. Mashat; Maulana, Rahman; Hari, Pasya; Purnama, Titis Mey; Aini, Paridatul; Khaeratullina (Alpatih Harapan Semesta, 2025)
This study aims to evaluate the implementation of the Berugak Belajar Programme in improving the reading literacy of students in grades 4 to 6 at SD Negeri 3 Masbagik Utara. The programme took place during break time between 3 October and 12 November 2024 in the Berugak Posko KKN and student assistance room. Using a descriptive qualitative approach, data was collected through observation and interviews, and analysed using the Miles and Huberman model. The results showed an increase in students' reading ability, interest, and confidence. The programme also encouraged students to actively discuss and understand the reading. Despite challenges such as time and weather constraints, the programme proved effective and is recommended for wider implementation.